Rancang Bangun Sistem Informasi (E- Monik) Berbasis Website Di MAN 1 Kota Bogor Menggunakan Metode Waterfall (Studi Kasus : MAN 1 Kota Bogor) - Muhamad Nur’ashad; Yulianti (CV. Shofanah Media Berkah, 2023)
MAN 1 Bogor City School in the current system is still using a manual system, Students bring cash and paper proof of payment which is then submitted and recorded by the clerk.Students get proof of payment that has been initialed by the clerk.Then the clerk records back in the ledger and copies it to Microsoft Excel.The design of this website-based E-Monic system. Where later this system can be a solution to these problems. The results obtained from testing using two methods of Black Box and White Box testing are that the web-based E Monic Financial Monitoring Information System at MAN 1 Bogor City School which was built both functionally and the structure of the program code can be run properly according to the expected functions even though there are still some features that are not added to complete the existing features. However, in general, the system created has fulfilled the main functions in data processing for the web-based E-Monic Financial Monitoring Information System, such as Create, Read, Update and Delete.